Nuclear protein kinase C isoforms and apoptosis - AM Martelli; G Mazzotti; S Capitani (European Journal of Histochemistry, 2009)
The process of apoptosis is regulated at multiple levels through phosphorylation by several different protein kinases. The protein kinase C (PKC) family of isozymes have been shown to exert both inhibitory and stimulatory influences on apoptosis. During the apoptotic process phosphorylative events are known to occur also at the nuclear level. Evidence suggests that PKC isoforms play a key role in some steps that lead to nuclear disassembly during the execution phase of apoptosis. This review highlights the recent progress made in determining the roles played by individual PKC nuclear isoforms in the control of apoptosis.